1990
DOI: 10.1246/bcsj.63.984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Starting Compositions on the Growth of Calcium Tungstate Crystals from Sodium Tungstate Flux

Abstract: Experimental evidence for the effect of starting compositions on the growth of CaWO4 crystals from Na2WO4 flux was given on the basis of the obtained solubility data. Crystal growth was conducted by heating mixtures at 1100°C for 5 h, followed by cooling to 500°C at a rate of 5°C h−1. Octahedral crystals up to 4.5 mm in size were grown. Mixture with ΔTSL(=TSoak temperature−TLiquidus temperature)=340°C produced 226 crystals measuring about 2.2 mm on the average. The crystal sizes decreased gradually and crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…However, the solubility could not be measured because the MoO 3 flux was volatile, and its mass decreased upon heating; it was thus difficult to measure the solubility of Al 2 O 3 in the MoO 3 flux. In general, in the case of a nonevaporable flux, both the solute crystal and the flux are held at a target temperature, and the solubility is measured based on the mass of flux and reduced solute. It is necessary to hold these at the target temperature for several hours to achieve equilibrium. However, this method cannot be applied to evaporative MoO 3 flux; therefore, we developed a new method to measure the solubility of Al 2 O 3 in MoO 3 flux at 1100 °C .…”
Section: Introductionmentioning
confidence: 99%
“…However, the solubility could not be measured because the MoO 3 flux was volatile, and its mass decreased upon heating; it was thus difficult to measure the solubility of Al 2 O 3 in the MoO 3 flux. In general, in the case of a nonevaporable flux, both the solute crystal and the flux are held at a target temperature, and the solubility is measured based on the mass of flux and reduced solute. It is necessary to hold these at the target temperature for several hours to achieve equilibrium. However, this method cannot be applied to evaporative MoO 3 flux; therefore, we developed a new method to measure the solubility of Al 2 O 3 in MoO 3 flux at 1100 °C .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other well-known scintillators, such as BaF 2 , CeF 3 and undoped CsI, , PbWO 4 crystal is most attractive for its high-energy physics applications because of its high density (8.28 g/cm 3 ), short radiation length ( X 0 = 0.92), fast decay time(≤10 ns) and excellent time and energy resolution. , PbWO 4 crystal has been investigated since the 1940s, but was studied as a heavy scintillator for high-energy physics only in the beginning of the 1990s due to the fact that the PbWO 4 scintillator was successfully chosen as a scintillating medium for electromagnetic (EM) colorimeters for the Compact Muon Solenoid (CMS) experiment at the Large Hadron Collider (LHC) by the Center of Europe for Research Nuclear (CERN). , Recently, PbWO 4 scintillator has become the most attractive candidate to build or upgrade several small setups for the intermediate energy region, where fast response and good energy resolution are required . As a matter of fact, the rare-earth element doped PbWO 4 has already been found to exhibit ion conductivity. , Previous studies have shown that PbWO 4 can be synthesized by several different techniques, such as a high-temperature solid-state reaction for powder, a flux method for whisker growth, the Bridgman method for single crystals, and so on. These techniques are technically demanding, as they require comparatively complex procedures to achieve ultrafine products.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, PbWO 4 crystals had been synthesized by several techniques, such as a high-temperature solid-state reaction for powder [22], a flux method for whisker growth [23], Czochralski [24], Bridgman methods [25], sol-gel [26], sonochemical route [27], microemulsion [28], hydrothermal [29], and so on. However, these methods are costly and need expensive equipments and high temperatures to synthesize and process.…”
Section: Introductionmentioning
confidence: 99%